RISK FACTORS FOR FOOT ULCERATION IN INDIVIDUALS WITH TYPE 2 DIABETES MELLITUS - Elen Ferraz Teston; Juliana de Souza Senteio; Beatriz Maria dos Santos Santiago Ribeiro; Edilaine Maran; Sonia Silva Marcon (Universidade Federal do Paraná, 2017)
The aim of this study was to analyze the factors associated with the risk of foot ulceration in individuals with type 2 diabetes mellitus. Quantitative study, with 71 individuals in a Primary Health Unit of a municipality in the state of Paraná. The data were collected through a home interview and a physical examination of the feet, from July to September 2016. The foot with risk of ulceration was identified in 35.2% of the studied population. The most prevalent risk factors for ulceration were inadequate nail cutting, use of inadequate footwear, presence of mycosis, callosities and cracked or dry skin. Inadequate capillary filling, loss of sensitivity and history of ulcers were associated with the risk of ulceration. Health professionals should recognize and value the importance of the foot examination and the provision of theoretical and practical guidance regarding foot care for individuals with diabetes.